What's in a first? The link between impromptu invitations and their responses. - Spyridoula Bella; Amalia Moser (Journal of Pragmatics, 2018)
This paper examines Greek invitations as first pair parts of an adjacency pair within the framework of Conversation Analysis. The focus of our research is on impromptu invitations issued via polar negative-interrogative constructions and the effects this type of con- struction has on the interactional organization of the whole invitation-response sequence. It is suggested that the issuing of the invitation by means of this particular syntactic choice has ramifications for the unfolding of the interaction with respect to sequencing and preference organization. Specifically, it is maintained that impromptu invitations issued by means of polar negative-interrogatives in Greek tend to trigger markedly delayed accep- tances. It is suggested that the explanation for this phenomenon lies in the “cross-cutting” preferences built in the construction when used to make impromptu invitations.